The influence of macroeconomic variables on sovereign sukuk yields: a panel data approach on selected Muslim countries - Rahman, Maya Puspa (2016)
The development of global sukuk market has been pioneered by Malaysia with the launch of the first sovereign 5-year global sukuk of US$600 million in 2002. Since then, the sovereign sukuk market has developed rapidly, with sovereign sukuk being issued by the Governments of Turkey, Qatar, Dubai, Bahrain and Indonesia to name a few. In view that sovereign security are not totally free from default such as the sovereign debt crisis of Greece, this paper attempts to unveil the behaviour of sovereign sukuk yields issued by the Muslim countries and whether they are influenced by the movement of the macroeconomic variables. By employing the panel data approach from 2006 to 2013, this study shows that only the inflation rate is able to explain the movement of the sovereign sukuk yields. The insignificance of other macroeconomic variables such as the GDP growth and money supply indicate that tagging the economic growth of the issuing country into the pricing of sovereign sukuk yields may not be feasible at this juncture. Being one of the most important topics to the regulator and market players, this study paves ways for more empirical analysis to be undertaken on the sovereign sukuk pricing mechanism.